Pengaruh Audit Judgement, Time Budget Pressure, Whitsleblowing System Terhadap Red Flag Dan Opini Audit - Rikhza Masfa’ani; Tri Ratnawati (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
This research aims to test the independent variable against the dependent variable. The object of this research was carried out at the Public Accounting Office in Surabaya City, using 60 auditors or respondents as research samples. In testing hypotheses to analyze and test data, this research used the SmartPLS application with Outer Model and Inner Model Testing. Produced research results regarding red flags (mediating variables) that audit judgment did not have a significant effect on red flags. Time budget pressure and the whistleblowing system have a significant influence on red flags. The variable on audit opinion (dependent variable) results in that audit judgment and time budget pressure do not have a significant effect on audit opinion and the whistleblowing system shows a significant effect on audit opinion. It is hoped that future researchers can add several variables.